Securement of central venous catheters by subcutaneously anchored suturless devices in neonates. (12th December 2022) - D'Andrea, Vito; Barone, Giovanni; Pezza, Lucilla; Prontera, Giorgia; Vento, Giovanni; Pittiruti, Mauro
Abstract: Background: Accidental dislodgement of central venous catheters is a frequent complication in NICU and it often requires catheter replacement. Subcutaneously anchored sutureless devices (SAS) have been recently introduced in clinical practice for securement of different types of central catheters, but they have never been used in neonates. We evaluated safety and efficacy of SAS in neonates. Methods: All neonates who required central venous catheters inserted via ultrasound-guided cannulation during 12 months of clinical practice in our NICU. We adopted SAS for securement of all central venous catheters inserted in neonates via ultrasound guided cannulation either of the brachio-cephalic vein (centrally inserted central catheters: CICC) or the femoral vein (femorally inserted central catheters: FICC). Results: seventy-two central catheters were inserted in 70 preterm and term neonates (3–4 Fr power injectable polyurethane catheters; 62 CICC + 10 FICC) and they were all secured with SAS. Mean postmenstrual age at the time of insertion was 31 weeks and mean weight was 1400 g. SAS was easy to place in all cases. The median duration of the line was 6 weeks. No accidental dislodgement of CICC or FICC was recorded. All SAS but one were left in place until elective removal of the catheter. In all patients, SAS removal was easy and uneventful, and it did not require any sedation or local anesthesia. Conclusions: SAS was effective in preventing accidental catheter dislodgement in 100% of cases. Complications during insertion, maintenance and removal were negligible.